Transplanted Neural Progenitor Cells from Distinct Sources Migrate Differentially in an Organotypic Model of Brain Injury - Ngalula, Kapinga P.; Cramer, Nathan; Schell, Michael J.; Juliano, Sharon L. (Frontiers in Neurology, 2015)
Brain injury is a major cause of long-term disability. The possibility exists for exogenously derived neural progenitor cells to repair damage resulting from brain injury, although more information is needed to successfully implement this promising therapy. To test the ability of neural progenitor cells (NPCs) obtained from rats to repair damaged neocortex, we transplanted neural progenitor cell suspensions into normal and injured slice cultures of the neocortex acquired from rats on postnatal day 0-3. Donor cells from E16 embryos were obtained from either the neocortex, including the ventricular zone (VZ) for excitatory cells, ganglionic eminence (GE) for inhibitory cells or a mixed population of the two. Cells were injected into the ventricular/subventricular zone (VZ/SVZ) or directly into the wounded region. Transplanted cells migrated throughout the cortical plate with GE and mixed population donor cells predominately targeting the upper cortical layers, while neocortically derived NPCs from the VZ/SVZ migrated less extensively. In the injured neocortex, transplanted cells moved predominantly into the wounded area. NPCs derived from the GE tended to be immunoreactive for GABAergic markers while those derived from the neocortex were more strongly immunoreactive for other neuronal markers such as MAP2, TUJ1, or Milli-Mark. Cells transplanted in vitro acquired the electrophysiological characteristics of neurons, including action potential generation and reception of spontaneous synaptic activity. This suggests that transplanted cells differentiate into neurons capable of functionally integrating with the host tissue. Together, our data suggest that transplantation of neural progenitor cells holds great potential as an emerging therapeutic intervention for restoring function lost to brain damage.